Development Challenges in the 1990s : Leading Policymakers Speak from Experience - Besley, Timothy; Zagha, Roberto (Washington, DC: World Bank and Oxford University Press, 2012)
This book brings together the insights and experiences of some of the world's leading policymakers and global thought leaders, individuals who have had substantial influence on the policy reforms and development strategies in their native countries. Sharing their unique perspectives, these practitioners of development explain the reasons for the uneven outcomes of the 1990s and, with the benefit of hindsight, draw relevant lessons for the future.